Rapid design of inclusive wireless technologies: A participatory workshop process. Issue 6 (2nd November 2022) - Jones, Brian; Gupta, Nandita; Persaud, Elizabeth; Phillips, Carolyn
ABSTRACT: Wireless technology products and services play a significant role in our everyday lives. Great advances in design features have improved the accessibility and utility of these technologies for older adults and people with disabilities. Yet, there is still opportunity to ensure upcoming designers of wireless technologies consider how their design helps or hinders their product's potential users. In this paper, we describe the evolution of a series of half-day participatory design workshops intended to expose student designers to real-world problem-solving alongside experts in the fields of aging and disability services and end users. Workshop attendees rapidly worked through an inclusive design process identifying and defining problems, considering the design requirements to meet the needs of various individuals, and finally designing and refining concepts to solve those problems. We describe the design of the workshops, iterations intended to improve on the experience, and our recommendations for conducting similar workshops